Problematika Angkringan Tradisional (AT) di Yogyakarta: Pembacaan Kondisi Empiris Angkringan Tradisional (AT) Menggunakan Konsep Modernitas dan Gentrifikasi - Rahman, M Bobby; Ibad, M Zainal; Wijayanti, Goldie Melinda (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Angkringan has become a cultural symbol, urban feature and social space for the people of Yogyakarta and its surroundings. However, deculturalization and modernity have been considered to be the main challenges for the existence of traditional angkringan (TA) in the city of Yogyakarta. This research aims to explain the potential problems faced by traditional angkringan in the midst of the urban modernity process that is occurring and its relationship with institutional attitudes towards modernity. This research was conducted around the university area of Gadjah Mada University and Yogyakarta State University. Data collection methods were carried out through field observations, informal interviews, and literature review data. The results of this research show that development with the concept of modernity which is interpreted in a limited way, the shift from informal spaces to formal spaces, business competition, technological developments and social changes have more or less influenced the existence of traditional angkringan. Apart from that, modernity can be said to have shifted the role, function and physicality of traditional angkringan from public spaces